Diagnosis Dan Patologi Infeksi Bakterial Vibrio Sp. Pada Ikan Kardinal Bangggai (Pterapogon Kauderni) - Mohammad Zamrud; Samliok Ndobe; Alimudin Laapo (Mitra Sains, 2017)
The aim of this study to observe the effect rearing time of Banggai cardinalfish were infected with Vibrio sp. from mortality rate and verify tissue’s abnormalities through histopathology test. Rearing time were 5, 10 and 15 days using a completely randomized design with three replications. Data processing is done by analysis of variance one-way ANOVA. Histology bacterial identification and data were analyzed descriptively. Research conducted at the Installation Building Fish Quarantine of Palu, Microbiology Laboratory of Palu and Histology Laboratory Fish Quarantine of Makassar in April to August 2015. Based on identification, found 8 bacteria of Vibrio sp were V. pelagius, V. damsela, V. carchariae, V. anguillarum, V. ordalii, V. parahaemolyticus, V. alginolyticus and V. aerogenes. The results showed rearing time for 15 days (treatment C) triggered the highest fatality rate of 62% was followed by rearing time 10 days (treatment B) of 52% and 5 days (treatment A) of 44%. Histopathological test showed tissue damage in the gills, kidney, skin and eyes. The results shows the longer rearing time the higher of mortality rate were infected with Vibrio sp.